Loss of Krox20 results in aortic valve regurgitation and impaired transcriptional activation of fibrillar collagen genes. (24th October 2014) - Odelin, Gaëlle; Faure, Emilie; Kober, Frank; Maurel-Zaffran, Corinne; Théron, Alexis; Coulpier, Fanny; Guillet, Benjamin; Bernard, Monique; Avierinos, Jean-François; Charnay, Patrick; Topilko, Piotr; Zaffran, Stéphane
Abstract: Aims: Heart valve maturation is achieved by the organization of extracellular matrix (ECM) and the distribution of valvular interstitial cells. However, the factors that regulate matrix components required for valvular structure and function are unknown. Based on the discovery of its specific expression in cardiac valves, we aimed to uncover the role of Krox20 ( Egr-2 ) during valve development and disease. Methods and results: Using series of mouse genetic tools, we demonstrated that loss of function of Krox20 caused significant hyperplasia of the semilunar valves, while atrioventricular valves appeared normal. This defect was associated with an increase in valvular interstitial cell number and ECM volume. Echo Doppler analysis revealed that adult mutant mice had aortic insufficiency. Defective aortic valves (AoVs) in Krox20 −/− mice had features of human AoV disease, including excess of proteoglycan deposition and reduction of collagen fibres. Furthermore, examination of diseased human AoVs revealed decreased expression of KROX20 . To identify downstream targets of Krox20, we examined expression of fibrillar collagens in the AoV leaflets at different stages in the mouse. We found significant down-regulation of Col1a1, Col1a2, and Col3a1 in the semilunar valves of Krox20 mutant mice. Utilizing in vitro and in vivo experiments, we demonstrated that Col1a1 and Col3a1 are direct targets of Krox20 activation in interstitial cells of the AoV. Conclusion: This study identifies a previously unknown function of Krox20 during heart valve development. These results indicate that Krox20-mediated activation of fibrillar Col1a1 and Col3a1 genes is crucial to avoid postnatal degeneration of the AoV leaflets.